Research Progress of circRNAs in Glioblastoma - Guo, Xu; Piao, Haozhe (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) are a class of single-stranded covalently closed non-coding RNAs without a 5' cap structure or 3' terminal poly(A) tail, which are expressed in a variety of tissues and cells with conserved, stable and specific characteristics. Glioblastoma (GBM) is the most aggressive and lethal tumor in the central nervous system, characterized by high recurrence and mortality rates. The specific expression of circRNAs in GBM has demonstrated their potential to become new biomarkers for the development of GBM. The specific expression of circRNAs in GBM has shown their potential as new biomarkers for GBM cell proliferation, apoptosis, migration and invasion, which provides new ideas for GBM treatment. In this paper, we will review the biological properties and functions of circRNAs and their biological roles and clinical applications in GBM.